Apresiasi dan Pembelajaran Unsur Intrinsik Teks Drama Mahkamah Siswa Kelas XI SMA - Rafika Aini; Sudirman Shomary (UIR Press, 2023)
This study aims to obtain information and data about the abilities and learning of students at SMA Negeri 1 Pekanbaru. The population in this study were 71 class XI students at SMA Negeri 1 Pekanbaru. The sample used is a purposive sample. The method used is descriptive method and quantitative approach. The techniques used are test techniques, interviews and observation. The test results from the research with an average score of 91.54 are in the very good category and the learning is in the very good category. After conducting a quantitative analysis of the research data regarding the ability to appreciate the intrinsic elements of the drama text